Analisis Ayat Al-Qur’an Terkait Pengaruh Fomo Terhadap Insecurity Gen Z - Nurul Hidayah; Nur Baitin; Widodo Hami (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
FOMO (Fear of Missing Out) refers to a form of fear and anxiety experienced by an individual concerning events occurring in a particular place, which subsequently gives rise to a compulsive desire to be present at the same location where something new or exciting is happening. The widespread emergence of this phenomenon has become one of the contributing factors to the increasing sense of insecurity among Generation Z in the modern era. This paper aims to present an analysis that demonstrates how the FOMO phenomenon serves as one of the root causes of insecurity among Gen Z adolescents. The author employs several Qur’anic verses that address ethical conduct toward oneself as a framework for offering solutions. The study adopts a quantitative approach, utilizing primary data obtained through interviews with several respondents, and secondary data drawn from various relevant literatures to support and enrich the discussion. The research findings indicate that Generation Z tends to fall short in applying the guidance presented in the Qur’an, despite the fact that the Qur’an offers clear and sound instructions regarding appropriate human behavior. Through this paper, the author provides evidence affirming that FOMO significantly contributes to the insecurities experienced by Generation Z—serving as a reflection of the lack of internalization of Qur’anic self-ethical teachings.